(untitled) - National Geographic Society (U.S.) (Washington, D.C., 2014)
From the changing shape of the warming northern polar region to the southern end of the globe in Antarctica, this atlas offers extraordinary new cartographic coverage of the entire globe. Through state-of-the-art maps and cutting-edge graphic design, this completely updated atlas covers the latest geopolitical developments and illuminates the important trends that grip the planet. From new political maps that review areas of turbulent civil strife in the Middle East to thematic spreads that highlight freshwater scarcity, climate and global warming, population growth, and more, this innovative book addresses the world's challenges and celebrates its wonders. Filled with dynamic infographics and compelling annotations and captions, NATIONAL GEOGRAPHIC GLOBAL ATLAS documents the critical facts, developments, and trends of our ever-evolving human and natural landscape.
Keywords: Tập bản đồ,Atlases